Insights into effects of sodium phytate on gut microbiome of mice by high-throughput sequencing - Lijuan Wu; Xiaoqing Lao; Yazeng Wu; Jing Zhang; Manyu Liang; Yanhong Yang; Xiaowei Gao (Biotechnology & Biotechnological Equipment, 2023)
Phytate, as the main phosphorus store in plant foods, is largely unavailable to monogastric animals, including humans, and has both adverse anti-nutritive and beneficial therapeutic effects for its consumers. The contradictory nature of phytate requires more caution when applying it. Administered phytate directly interacts with and affects gut microbiota, which has essential roles in host health. In this study, we investigated the effects of sodium phytate on the gut microbiome of mice by high-throughput sequencing. Mice were orally gavaged with 8 mg or 40 mg of sodium phytate per day for 4 weeks. The results indicate that phytate administration reduced the growth performance of mice in a dose-dependent manner. The diversity and composition of the gut microbiota in mice were significantly altered by phytate intake. Phytate promoted the growth of certain probiotics and inhibited that of some pathogens. Phytate did not cause obvious functional changes in the gut microbiota but reduced the abundance of inositol-phosphate-synthase–producing bacteria. Our results provide additional insights into the health-promoting effects of phytate on consumers.